Hubungan Keterampilan di Abad 21 Terhadap Peningkatan Kompetensi Kepala Sekolah di Kota Gorontalo - Agustini Agustini; Roskina Roskina (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
In the 21st century, school leaders are expected to be able to streamline school administration, including developing the teaching and learning process. School administrators must have special skills and skills that are superior and different from previous school administrators. This research aims to examine the relationship between skills in the 21st century and increasing the competency of Gorontalo City school principals. The research method used is quantitative research with a survey approach. The participants in this research were 30 school principals in Gorontalo City who were chosen randomly. Data was collected through a questionnaire that assessed skills in the 21st century and increased competency of school principals. Data analysis was carried out using correlation statistical techniques to determine the relationship between these variables.